RETHINKING ISLAM THROUGH INTERNALIZATION OF INSIGHTS INTO ISLAMIC UNIVERSALITY IN ISLAMIC THEOLOGY : PEMBAHARUAN PEMIKIRAN ISLAM MELALUI INTERNALISASI WAWASAN UNIVERSALITAS ISLAM DALAM TEOLOGI ISLAM - Asnan Purba; Akhmad Jazuli Afandi (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2022)
This article seeks to discuss the renewal of thought into a Muslim (internal renewal) through theinternalization of universal insights in Islam. Islamic declarations and statements are universal andflexible to the demands of the times will be realized through understanding and understanding ofIslam itself in a kaffah (comprehensively). This research is a conceptual study by utilizing sources ofliterature. The author will review data from the source of the library with various points of view todetermine the value of Islamic universality, including in terms of theology, law, humanity,anthropology, and psychology. The author will carry out internalization efforts through thecultivation of a strong understanding of insight into Islam. Thus a Muslim will be able to renew thepattern of thinking precisely according to the purpose because renewal without insight is nonsense